Izhodišča za proučevanje kakovosti podatkov v bibliografskih in normativnih zapisih - Badovinac, Branka (Knjižnica, 2017)
Purpose: The aim of the study is to explore starting points in researching the quality of data in bibliographic and authority records, specifically 1) how is the concept of data quality determined in cataloguing field, 2) what are basic theoretical concepts of data quality, and 3) what are research directions in data quality according to the contemporary professional literature in cataloguing (including digital libraries). Methodology/approach: The first two parts are designed in exploratory research manner, the third part has been conducted by literature review of contemporary works in the field of cataloguing in the years 2003-2016. Results: Five main factors were identified in comprehension of data quality in the field of cataloguing: users, contents and format standards, workflow rationalization, cataloguers, and cataloguing technology. From the theoretical basis the contemporary literature was disposed in the following viewpoints: determining the data problems, dimensions, metrics and evaluation, quality assessment and study interpretations, and techniques and activities of data enhancement. The results are showing trends in the extension of possible dimensions and development in automatic metric and evaluation. Moreover, the subjective evaluation from the expert point of view has been highlighted. Research limitation: Because of the extensiveness of the research question and the arbitrariness in selecting the sources, some issues have not been explored in detail. Originality/practical implications: The study is filling up some theoretical gaps in researching data quality.
Keywords: cataloguing; katalogizacija; data quality; kakovost podatkov; metadata; metapodatki; bibliografski zapisi; bibliographic records; normativni zapisi; authority records